Sycidiphaga, a new genus of Sycophaginae Walker, 1975 (Hymenoptera, Chalcidoidea, Agaonidae) associated with Ficus subgenus Sycidium in southern China - Liu, Yang; Rasplus, Jean-Yves; Noort, Simon Van; Li, Zi; Huang, Dawei (Zootaxa, 2017)
A new genus of Sycophaginae (Hymenoptera: Agaonidae), Sycidiphaga Liu, Rasplus & Huang n. gen., is described with a single new species, S. cyrtophyllae Liu, Rasplus & Huang n. sp. This species was discovered in Yun Nan and Gui Zhou, China and is associated with Ficus cyrtophylla (Moraceae, Ficus, subgenus Sycidium). The new taxon is readily distinguished from other genera of Sycophaginae by: 1) the presence of a conspicuous interantennal blade-like projection that extends well above the level of the toruli; 2) an inflated parastigma surrounded by a slight infuscation of the wing membrane; 3) the presence of a long and conspicuous median sulcus on the male pronotum; and 4) the presence of dense and long pilosity on the wings. Illustrations and a diagnosis and description of Sycidiphaga are provided, as is a key to the world genera of Sycophaginae. The phylogenetic position of Sycidiphaga was demonstrated through sequencing four gene regions of COI, Cyt b, 28s D3-D5 and EF-1α genes and conducting a phylogenetic analysis of available sequences for the subfamily. Sycidiphaga cannot be placed with confidence within Sycophaginae but several discussed characters suggest a close relationship with Idarnes Walker and Sycophaga Westwood. Interactive Lucid identification keys are available online at www.figweb.org.